THE ROLE OF PROJECT MANAGEMENT IN SUSTAINING COMPETITIVE ADVANTAGE-A FIELD STUDY IN CELLULAR COMMUNICATION COMPANIES IN IRAQ - Raghad Adnan Mahdi; Dr. Emman Mazyad (Scholars Digest Publishing, 2024)
This study aims to determine the role of project management and the sustainability of competitive advantage. A sample of /106/ workers was purposively selected, and a questionnaire was used as a data collection tool. The questionnaire consisted of more than 40 questions distributed across the dimensions of the paper, while the study yielded the main results. The success factors of project management combined with its integrated dimensions (leadership, risk-taking, government support) positively impact the company's sustainable competitive advantage in terms of its integrated dimensions (efficiency, customer orientation). The study concluded that mobile communications in Iraq is a crucial recommendation to continue the integrated interest of telecommunication companies in project management as it plays a positive role in achieving sustainable competitive advantage and provides an opportunity to reach a customer base different from all competitors.
Keywords: project management, competitive advantage, cellular companies.